2014
DOI: 10.4103/0019-509x.175361
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility profile of Gram-negative bacteremic isolates to beta lactam-beta lactamase inhibitor agents in comparison to other antibiotics

Abstract: Findings of the study make a strong argument for using BL-BLI agents and sparing carbapenem to curtail the spiraling scenario of carbapenem resistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 4 publications
4
1
0
Order By: Relevance
“…Surprisingly, cefoperazone /sulbactam and cefepime/tazobactam performed comparatively better than carbapenems against Pseudomonas. Similar to our observations, Abdul et al [15] have also reported that BL-BLI combinations performed better than carbapenems against pseudomonas.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Surprisingly, cefoperazone /sulbactam and cefepime/tazobactam performed comparatively better than carbapenems against Pseudomonas. Similar to our observations, Abdul et al [15] have also reported that BL-BLI combinations performed better than carbapenems against pseudomonas.…”
Section: Discussionsupporting
confidence: 92%
“…The antibiotic susceptibility reported by Abdul et al [15] for different antibiotics tested is also almost similar to our pattern. Increase in carbapenems resistance has been linked with excessive carbapenem consumption.…”
Section: Discussionsupporting
confidence: 92%
“…Addition of tazobactam increased the susceptibility of from 32% to 90% in E. coli, from 16 to 41.0% in Klebsiella, from 86.0 to 87% in Pseudomonas and Proteus from 80% to 100%. This study highly correlates with Abdul Kafur et al 13 Cefepime/tazobactam having better coverage than Cefepime, Cefoperazone-sulbactam, Piperacillin Tazobactam and Ceftazidime Tazobactam correlates with my previous sudy. 14 Cefepime tazobactam (30/10 μg) combination was found to be very effective against many ESBL producing Gram negative organism.…”
Section: Discussionsupporting
confidence: 89%
“…8,9 Very few previous Indian studies have evaluated and compared the in -vitro activity of the following three βlactam and β-lactamase inhibitor combinations piperacillin-tazobactam, cefoperazone sulbactam and cefepime tazobactam. In the present study, cefepime tazobactam has better susceptibility than the other two BL/BLI combination tested, same was reported by Sood S et al, and Abdul K et al 9,10 Further, it has also been demonstrated in this study that in comparison to cefepime the cefepime-tazobactam combination exhibited good activity against E. coli, Klebsiella pneumoniae, Acintobacter baumanii as well as Pseudomonas aeruginosa. The increased susceptibility percentage of cefepime in combination formulation with tazobactam was also shown by Sood S et al, and Susan M et al 9,11 The current data reveals an interesting picture of a very comparable susceptibility of Enterobacteriaceae (fermenters) to CPM/TZ (77.2%) and carbapenems (82.5% to 83.5%).…”
Section: Discussionsupporting
confidence: 89%